The fifth doctrine [compact disc, unabridged] - Robards, Karen (Brilliance Audio, Inc., 2019)
After everything she's seen, Bianca knows feeding fake information directly into the belly of the beast is about as dangerous as it gets. It could mean torture or endless imprisonment, assuming she survives. But it might also ignite the kind of chaos that forces a revolution. It might just change the world. Besides, if Bianca has to go down, she's gonna go down swinging.